2017
DOI: 10.7567/jjap.56.04cs04
|View full text |Cite
|
Sign up to set email alerts
|

Potential-induced degradation of thin-film Si photovoltaic modules

Abstract: Potential-induced degradation (PID) of thin-film Si photovoltaic (PV) modules was investigated. The characteristics of PID phenomena of thin-film Si PV modules are markedly different from those of crystalline Si PV modules. Not only performance loss but also linear-shape and spot-shape delamination was observed after negative voltage application. Recovery from PID was also observed after positive voltage application. However, rapid progression of PID was found after the second negative voltage application afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
0
19
1
1
Order By: Relevance
“…This, too, suggests that there was no significant increase in the recombination losses. This PID, mainly caused by optical losses, is different from all the other PID-related phenomena reported so far (while PID in thin-film a-Si PV modules is partly affected by additional optical losses, other loss mechanisms dominate 25 ). A possible reason behind the reduced J sc will be discussed in detail in Section 4.2.…”
Section: Degradation Behavior Of Shj Pv Modulescontrasting
confidence: 85%
See 3 more Smart Citations
“…This, too, suggests that there was no significant increase in the recombination losses. This PID, mainly caused by optical losses, is different from all the other PID-related phenomena reported so far (while PID in thin-film a-Si PV modules is partly affected by additional optical losses, other loss mechanisms dominate 25 ). A possible reason behind the reduced J sc will be discussed in detail in Section 4.2.…”
Section: Degradation Behavior Of Shj Pv Modulescontrasting
confidence: 85%
“…It has been reported that various kinds of PV cells, such as conventional p-type c-Si, [10][11][12][13][14] n-type front-emitter c-Si, [15][16][17][18][19] n-type rear-emitter c-Si, 19,20 n-type IBC c-Si, 22 a-Si thin-film, 24,25 CIGS thinfilm, [26][27][28] and CdTe thin-film 28,29 PV cells, undergo PID under negative bias. Herein, we first clarified how the J-V, EQE, and EL characteristics of SHJ PV modules change upon applying a negative bias.…”
Section: Degradation Behavior Of the Shj Pv Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…If the encapsulant with a relatively low volume resistivity on the order of 10 14 Ω cm, such as ethylene-vinyl acetate (EVA), is used, leakage current flows from the Al frame to the PV cells accompanied by a drift of Na from the cover glass to the PV cell. Such Na drift by a high electric field and migration to the pn junction in the PV cells are one of the possible origins of PID for p-type crystalline Si PV modules, [4][5][6][7] although PID is merely a generic name for the degradation induced by the potential difference between the Al frame and the PV cells, and the degradation behavior and mechanism of PID are essentially different for different types of PV cells: for p-type crystalline Si, 1,2,7,8) possibly due to the migration of Na; for n-type crystalline Si, [9][10][11][12] possibly due to charge recombination; for Si heterojunction, 13,14) due to the reduction of transparent conductive oxide (TCO) layer; thin-film Si, 15) due to the delamination of the TCO layer, Cu(In,Ga)Se 2 , 16,17) CdTe, 18) and others. Such mechanisms are still controversial in spite of much effort using various kinds of tools and techniques devoted to clarifying the main origins of PID.…”
Section: Introductionmentioning
confidence: 99%